2010
DOI: 10.4028/www.scientific.net/amm.24-25.65
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Hollow Langevin Transducer for Ultrasonic Coring

Abstract: Abstract. A number of architectures for a hollow Langevin ultrasonic transducer are proposed and evaluated. One of these is optimised by finite element modelling and is then manufactured and analysed experimentally. The preload on the transducer ceramics is increased and the effect on the performance is measured. At maximum preload the results of an experimental modal analysis are used to determine the natural frequency and response of both the operating longitudinal mode and unwanted bending modes. The perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As expected, it is observed that both resonance and antiresonance are increased along with the mechanical pre-stressing (Arnold and Mu¨hlen, 2001a;Fu, 2005;Harkness et al, 2010). The variations of resonance value decreased when the mechanical pre-stress increased, thus leading to a tendency of stabilization.…”
Section: Preliminary Results: Resonances and Impedancesmentioning
confidence: 52%
See 3 more Smart Citations
“…As expected, it is observed that both resonance and antiresonance are increased along with the mechanical pre-stressing (Arnold and Mu¨hlen, 2001a;Fu, 2005;Harkness et al, 2010). The variations of resonance value decreased when the mechanical pre-stress increased, thus leading to a tendency of stabilization.…”
Section: Preliminary Results: Resonances and Impedancesmentioning
confidence: 52%
“…There are a few recent studies on the influence of the mechanical pre-stressing on piezoelectric transducers (Adachi et al, 1998;Arnold and Mu¨hlen, 2001a;DeAngelis et al, 2015;Fu and Li, 2009;Han et al, 2008;Harkness et al, 2010;Jiang et al, 2017;Qiao and Wang, 2010;Xu et al, 2002). Some studies focus on experimental reports (Arnold and Mu¨hlen, 2001a;Qiao and Wang, 2010) with procedures and results relative to the resonances and impedances determination.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Rod-type PETs, or Langevin-type, in their design contain a rear mass, piezoelectric ceramics and a radiating mass. Such transducers are used both in a liquid medium, for example, in underwater acoustics, and in the air -ultrasonic technological equipment, an ultrasonic motor, a piezotransducer, some medical equipment [1], rock drilling devices [2]. During operation, the transducer is subjected to opera-tional loads -electrical, mechanical, cavitation, thermal.…”
Section: Introductionmentioning
confidence: 99%